Cell Wall Reinforcements Accompany Chilling and Freezing Stress in the Streptophyte Green Alga Klebsormidium crenulatum - Steiner, Philip; Obwegeser, Sabrina; Wanner, Gerhard; Buchner, Othmar; Lütz-Meindl, Ursula; Holzinger, Andreas (Frontiers in Plant Science, 2020)
Adaptation strategies in freezing resistance were investigated in Klebsormidium crenulatum, an early branching streptophyte green alga related to higher plants. Klebsormidium grows naturally in unfavourable environments like alpine biological soil crusts, exposed to desiccation, high irradiation and cold stress. Here, chilling and freezing induced alterations of the ultrastructure were investigated. Control samples (kept at 20 °C) were compared to chilled (4 °C) as well as extracellularly frozen algae (-2 °C, -4 °C). A software-controlled laboratory freezer (AFU, automatic freezing unit) was used for algal exposure to various temperatures and freezing was manually induced. Samples were then high pressure frozen and cryo-substituted for electron microscopy. Control cells had a similar appearance in size and ultrastructure as previously reported. While chilling stressed algae only showed minor ultrastructural alterations, such as small inward facing cell wall plugs and minor alterations of organelles, drastic changes of the cell wall and in organelle distribution were found in extracellularly frozen samples (-2 °C, -4 °C). In frozen samples, the cytoplasm was not retracted from the cell wall, but extensive three-dimensional cell wall layers were formed, most prominently in the corners of the cells, as determined by FIB-SEM and TEM tomography. Similar alterations/adaptations of the cell wall were not reported or visualized in Klebsormidium before, neither in controls, nor during other stress scenarios. This indicates that the cell wall is reinforced by these additional wall layers during freezing stress. Cells allowed to recover from freezing stress lost these additional cell wall layers, suggesting their dynamic formation. The composition of these cell wall reinforcement areas was investigated by immuno-TEM. In addition, alterations of structure and distribution of mitochondria, dictyosomes and a drastically increased endoplasmic reticulum were observed in frozen cells by TEM and TEM tomography. Measurements of the photosynthetic oxygen production showed an acclimation of Klebsormidium to chilling stress, which correlates with our findings on ultrastructural alterations of morphology and distribution of organelles. The cell wall reinforcement areas, together with the observed changes in organelle structure and distribution, are likely to contribute to maintenance of an undisturbed cell physiology and to adaptation to chilling and freezing stress.